Qualidade de vida, estado nutricional e capacidade para a tomada de decisão em idosos institucionalizados e não institucionalizados de Santa Cruz do Sul/RS - Deon, Rúbia Garcia (2015)
Introduction: The population aging process is growing in Brazil, and one of the important factors in this context is the institutionalization, which can reduce life quality, make it difficult to maintain a healthy weight and affect the decision-making capacity for the elderly. Objective: To evaluate life quality, nutritional status and decision-making capacity in institutionalized and non-institutionalized elderly of the city Santa Cruz do Sul in the Brazilian state of Rio Grande do Sul. Method: Transversal, descriptive and analytical study. The inclusion criteria were to be older than 60 years and live in the city of Santa Cruz do Sul. The exclusion criteria were being hospitalized at the time the survey was being conducted, or not being able to understand or to express their choices to the questions included in the instruments used. The data collection occurred in long-term care institutions for elderly and at the Family Health Strategies of the city of Santa Cruz do Sul in the Brazilian state of Rio Grande do Sul, with pairing criteria by age, gender, education and whether or not bedridden. The instruments used were the Mini Nutrition Examination, the Body Mass Index, the Psychological-Moral Development, the WHOQOL-BREF and WHOQOL-OLD. For the statistical analysis the software Excel and SPSS 18.0 were used. The associations between the variables were performed using the chi-square tests, linear correlation and ANOVA, with statistical significance of 5% (P <0.05). This study was approved by the Ethics Committee of the PUCRS, with CAAE number 11986413.5.0000.5336 and all the participants signed the Free and Informed Consent form. Results: 552 elderly were evaluated, 276 institutionalized and 276 non-institutionalized, with an average age of 76.83 ± 7.36 years old. Most were women (55.4%), with basic education (49.7%) and not bedridden (98.5%). In the life quality assessment, the average of WHOQOL-BREF was 13.59 ± 2.92, the WHOQOL-OLD was 46.09 ± 4.71 and associations with the institutionalization were statistically significant (p <0.05 ). In the nutritional status assessment by the Mini Nutritional Examination the majority (61,6%) was eutrophic, by the Body Mass Index (49,1%) were overweight and associations with the institutionalization were statistically significant (p <0.001). The Psychological-Moral Development evaluation has shown that all participants had the capacity for decision-making and the association with the institutionalization was statistically significant (p = 0.0001). Conclusions: The study of the results of this research shows relevant data and can guide for performing early intervention and contribute to the training of professionals for the real needs of this population.